Research Engagement among EFL Teachers at Public Schools in Saudi Arabia - Alenezi, Maryumah (Dirasat: Educational Sciences, 2021)
The present study investigates involvement in research by English as a Foreign Language (EFL) teachers, the impact of research practice on teachers’ professional development and teaching competencies, and the effects of demographic variables on both reading and research. The study applied a questionnaire adapted from Borg (2009). The participants were EFL teachers (n= 152) from public schools in Saudi Arabia. Following a descriptive-analytical research design, the results showed that the majority of teachers (41%) “sometimes” read research articles. There were statistically significant differences in reading research due to their qualifications and interest in taking research methods courses. On the contrary, there were no statistically significant differences due to experience, teaching grade, and weekly hours of instruction. Additionally, most teachers (35%) “sometimes” conduct scientific research. There were statistically significant differences in conducting scientific research due to weekly hours of instruction and knowledge of research methods, whereas there were no statistically significant differences due to experience, grade the teacher teaches, or educational qualifications. Practical implications and recommendations for future research were provided.